ON THE CORRELATION BETWEEN FEDERAL EDUCATIONAL STANDARDS AND PROFESSIONAL STANDARDS: PROBLEMS, POSSIBLE APPROACHES, RECOMMENDATION ON ACTUALIZATION - Sergey A. Pilipenko; Aleksandr A. Zhidkov; Evgeniya V. Karavaeva; Alexandra V. Serova (Высшее образование в России)
The article addresses the issues of professional standards application under the actualization of state educational standards in the context of legislative changing as relative to allowance of professional standards in the professional education system. The authors report on methodological approaches to the actualization of the federal state educational standards of higher education and exemplary basic educational programs.